2020
DOI: 10.3390/ijms21114144
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Disturbance in Fatty Liver Energy Metabolism Converges on IGFBP2 Abundance and Regulation in Mice and Men

Abstract: Fatty liver occurs from simple steatosis with accumulated hepatic lipids and hepatic insulin resistance to severe steatohepatitis, with aggravated lipid accumulation and systemic insulin resistance, but this progression is still poorly understood. Analyses of hepatic gene expression patterns from alb-SREBP-1c mice with moderate, or aP2-SREBP-1c mice with aggravated, hepatic lipid accumulation revealed IGFBP2 as key nodal molecule differing between moderate and aggravated fatty liver. Reduced IGFBP2 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
(90 reference statements)
1
16
2
1
Order By: Relevance
“…This observation is in line with human studies, as serum/plasma levels of IGFBP2 decreased in obese males and females and obese men with NAFLD and NASH compared with the non-obese control group [60,58]. Reduced level of IGFBP2 is along with decreased oxidation of fatty acids and enhanced de novo lipogenesis in hepatocytes [58].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This observation is in line with human studies, as serum/plasma levels of IGFBP2 decreased in obese males and females and obese men with NAFLD and NASH compared with the non-obese control group [60,58]. Reduced level of IGFBP2 is along with decreased oxidation of fatty acids and enhanced de novo lipogenesis in hepatocytes [58].…”
Section: Discussionsupporting
confidence: 88%
“…The IGFBP2 promoter was hypermethylated, and its mRNA expression downregulated in a mouse model of fatty liver; therefore, secretion of hepatic IGFBP2 and plasma level of IGFBP2 reduced [58]. This observation is in line with human studies, as serum/plasma levels of IGFBP2 decreased in obese males and females and obese men with NAFLD and NASH compared with the non-obese control group [60,58]. Reduced level of IGFBP2 is along with decreased oxidation of fatty acids and enhanced de novo lipogenesis in hepatocytes [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are also supported by a recent cohort study indicating that IGFBP2 levels are inversely associated with the risk of NAFLD [ 91 ]. Similarly, Fahlbusch et al demonstrated that circulating levels of IGFBP2 are lower in patients with NAFLD and NASH, and are restored after weight loss following bariatric surgery along with reductions in hepatic fat content [ 92 ]. A recent epigenomic study suggested that differentially methylated genes might distinguish patients with advanced NASH from simple steatosis [ 93 ].…”
Section: Epigenetic Mechanisms Underlying the Link Between Nutrition And Aberrant Gene Expression In Nafldmentioning
confidence: 99%